Applications of Cytogenetic and Fragile X Molecular Testing in Individuals with Mental Retardation - Özbey, Ülkü; Yüce, Hüseyin; Kara, Murat (Fırat University, 2007)
Objectives: The fragile X syndrome (FXS) is the most frequent cause of inherited mental retardation (MR). It is caused by the progressive expansion of (CGG)n trinucleotide repeats located in the promoter region of the (Fragile X mental retardation 1 gene) FMR1 gene at Xq27.3. The aim of the study is to estimate the prevalance of the FXS and other chromosomal aberrations by cytogenetic and molecular analysis in patients with MR and language disorders. Material and Method: 72 cases with MR who were sent to our laboratory for molecular and cytogenetic search in term of fragile X. The lymphocyte culture was carried out according to standard methods. DNA extraction was done using whole blood DNA extraction kit (Bangalore Genei, Bangalore). This was followed by bisulphite treatment and PCR amplification. Results: Chromosome abnormality was found in 12 cases (16.7%). 7 cases (9.7%) were detected fragile X positive in molecular analysis. The mutations were detected such a full mutation and abnormal methylation in (4.1%) and a premutation carrier (5.5%). We concluded that chromosomal studies in mentally retarded patients help in accurate diagnosis and proper prognosis followed by genetic counseling and management rehabilitation. Conclusion: Due to recent molecular advances, our understanding of the perplexing genetic issues surrounding fragile X syndrome has grown and diagnostic techniques have become both reliable and readily available. ©2007, Fırat University, Medical Faculty

Amaç: Kalıtsal mental retardasyonun (MR) en yaygın sebebi Frajil X Sendromu'dur (FXS). Xq27.3'deki (Frajil X mental retardasyon 1) FMR-1 geninin promotor bölgesinde yer alan (CGG)n üçlü nükleotid tekrar sayısının artmasıyla bu bozukluk meydana gelmektedir. Bu çalışmanın amacı, MR ve konuşma güçlüğü bozukluğu olan vakalarda, sitogenetik ve moleküler analizlerle diğer kromozomal anormallikler ve FXS'unun insidansını ortaya koymaktır. Gereç ve Yöntem: Laboratuarımıza Frajil-X açısından sitogenetik ve moleküler araştırma için yollanan MR'lu 72 olgu çalışıldı. Lenfosit kültürü standart metodlara göre yapıldı. DNA ekstraksiyonu, tüm kandan DNA ekstraksiyon kit (Bangalore Genei, Bangalore) kullanılarak yapıldı. Bunu bi sülfitle muamele ve (polimeraz zincir reaksiyonu) PZR amplifikasyonu izledi. Bulgular: 12 olguda (%16.7) kromozomal anomali bulundu. 7 olguda (%9.7) moleküler analizde frajil X pozitif olduğu tespit edildi. %4.1'inde tam mutasyon ve anormal metilasyon ve %5.5'inde premutasyon taşıyıcısı olduğu saptandı. Mental geriliğe sahip hastalarda genetik danışma ve yönetim rehabilitasyonu tarafından yapılan kromozomal çalışmaların doğru tanı ve düzenli prognoza yardımcı olduğu sonucuna vardık. Sonuç: Son zamanlardaki moleküler ilerlemelere bağlı olarak, frajil X sendromunu da kapsayan zihni karıştırıcı genetik konularını daha kolay anlamaktayız. Böylece diagnostik teknikler hem güvenilir hem de kolay ulaşılabilir hale gelmiştir. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Mental Retardasyonlu Bireylerde Sitogenetik ve Frajil X Moleküler Testlerin Uygulanması